From an Antique Land : an Introduction to Ancient Near Eastern Literature. - Ehrlich, Carl S.; Beckman, Gary.; Foster, Benjamin R.; Hollis, Susan Tower; Kottsieper, Ingo.; Pitard, Wayne T.; Rubio, Gonzalo (Lanham : Rowman & Littlefield Publishers, 2009)
From an Antique Land introduces the various cultures and literatures of the Ancient Near East, including literature originally written in Egyptian, Sumerian, Akkadian, Hittite, Ugaritic, Canaanite, Hebrew, and Aramaic. The timeframe extends from the invention of writing through the conquest of Alexander the Great. Each chapter includes an overview of the culture, a discussion of literary genres, and descriptions and short analyses of the major literary works.
Cover; Title Page; Copyright Page; Dedication Page; Table of Contents; List of Abbreviations; Preface; Chapter 1: Introduction; Chapter 2: Sumerian Literature; Chapter 3: Egyptian Literature; Chapter 4: Akkadian Literature; Chapter 5: Hittite Literature; Chapter 6: Canaanite Literature; Chapter 7: Hebrew/Israelite Literature; Chapter 8: Aramaic Literature; Bibliography; Index; About the Editor and Contributors.
Print version record.
Includes bibliographical references (pages 445-492) and index.
Master record variable field(s) change: 050
Keywords: Middle Eastern literature -- History and criticism; Oriental literature -- History and criticism; Middle Eastern literature -- History and criticism; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Middle Eastern literature; Oriental literature; Electronic books; Criticism, interpretation, etc